If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3f + 2 = 3(-2) + -8f Reorder the terms: 2 + -3f = 3(-2) + -8f Multiply 3 * -2 2 + -3f = -6 + -8f Solving 2 + -3f = -6 + -8f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '8f' to each side of the equation. 2 + -3f + 8f = -6 + -8f + 8f Combine like terms: -3f + 8f = 5f 2 + 5f = -6 + -8f + 8f Combine like terms: -8f + 8f = 0 2 + 5f = -6 + 0 2 + 5f = -6 Add '-2' to each side of the equation. 2 + -2 + 5f = -6 + -2 Combine like terms: 2 + -2 = 0 0 + 5f = -6 + -2 5f = -6 + -2 Combine like terms: -6 + -2 = -8 5f = -8 Divide each side by '5'. f = -1.6 Simplifying f = -1.6
| -4=n/-3-7 | | 7/2*2/49 | | 1-3(2c+d)+4(c-4d)= | | 50/2.5 | | 4-y=25 | | -3(6y-10)-y=-2(y-5) | | 6(x+1)/3=4X-1 | | -8+n/15=-9 | | 40+25=15+30 | | 9z-5-4z=-5 | | 20,50= | | 1/5+2 | | x/4+x/3=9/4 | | 5ln(x+3)=0 | | 3(2x-1)+4=5x | | 17=2x-15+x+8 | | -5y=4 | | 5x+1=2(2x+7) | | -12x+3x-109=143 | | 981+(45g*9)/(5*5)+9514=900000 | | 2+-5+-3=-6 | | -4(2y-3)-y=-2(y-5) | | 2+-5+-3= | | 41/45-1/27 | | 5x(6)-4= | | 3a-4a=4 | | -8=x/-7-10 | | -8=x/-7-10 | | X-6+x=10 | | -(-9)-5+(4)= | | -75+9x-x=69 | | 7/5*5/14 |